RANCANG BANGUN SISTEM INFORMASI KEHADIRAN DALAM MENDUKUNG GOOD UNIVERSITY GOVERNANCE (Studi Kasus pada ST3 TELKOM) - Supriyadi, Didi (Proceeding SENDI_U, 2015)
Development of ICT is very helpful to increase performance and business processes of organization. It must generateusefulness in obtaining information for stakeholders, also assist organization to get feedback from stakeholders. It shouldassist manager of organization to make or support decision making. Changes in the shape of higher education institutions areexpected to push each college to have a better management. It is necessary for the implementation of the concept of highereducation institutions that are considered to be ideal, known as Good University Governance (GUG). One of the businessprocesses that happen at ST3 Telkom Purwokerto is the management of human resources. One of HR management activitiesat ST3 Telkom is manage of employee attendance. Currently, System that manages attendance of ST3 Telkom employee stilldoesnât support GUG principle that can be used by stakeholders. The researcher intends and deems it necessary to developthe presence of information systems that support the concept of GUG using Waterfall method. Information system whichhas developed, has been testing by black box methods. The results show that the system is able to display the presenceinformation of officials ST3 Telkom on information board (dashboard). It can be exploited by stakeholders in order to realizeone of the responsibility principle of GUG. This system can be further developed and integrated for employee payroll system.Keywords: information systems, presence, waterfall, good university governance